2018
DOI: 10.1016/j.ijpharm.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Freeze drying of polyelectrolyte complex nanoparticles: Effect of nanoparticle composition and cryoprotectant selection

Abstract: This work investigates the impact of nanoparticle (NP) composition and effectiveness of cryo-/lyo-protectants in a freeze drying process, which was employed to convert liquid dispersions of polyelectrolyte complex (PEC) NPs into completely redispersible powders. PEC NPs, with and without peptide, were produced by complex coacervation. The cryo-/lyo-protectants investigated were mannitol, trehalose (TRE) and poly(ethylene glycol) (PEG). The solid state of lyophilised powders was studied by thermal analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…It was suggested that, while all the carrageenans studied are able to form polyelectrolyte complexes with PROT, the mechanism of complexation was different for iota carrageenan (Dul et al 2015). Additionally, another reports show a large shift in the amide I band of chitosan, observed after its complexation with HA (Umerska et al 2012), chondroitin sulphate (Umerska et al, 2015) and after complexation of chitosan with kappa carrageenan (Li et al 2013). Therefore, it appears that AAL is another polyanion that has an ability to bind to PROT via electrostatic interactions.…”
Section: Interactions Between Alginate and Protmentioning
confidence: 98%
See 2 more Smart Citations
“…It was suggested that, while all the carrageenans studied are able to form polyelectrolyte complexes with PROT, the mechanism of complexation was different for iota carrageenan (Dul et al 2015). Additionally, another reports show a large shift in the amide I band of chitosan, observed after its complexation with HA (Umerska et al 2012), chondroitin sulphate (Umerska et al, 2015) and after complexation of chitosan with kappa carrageenan (Li et al 2013). Therefore, it appears that AAL is another polyanion that has an ability to bind to PROT via electrostatic interactions.…”
Section: Interactions Between Alginate and Protmentioning
confidence: 98%
“…No considerable difference in the colloidal stability of anionic NPs was observed in the acetate, HEPES and diluted PBS media, even though the concentration of the PBS solution was over a 6-fold lower (0.1M versus 0.015M) than the other two solutions. This might be contributed to the more kosmotropic (order inducing) character of the acetate and 4-(2-hydroxyethyl)-1-piperazineethanesulphonate (HEPES) anions, while the chloride anion is considered more chaotropic (order disrupting) (Umerska et al 2015). Thus lower concentrations of the chloride anions are needed to induce physical instability of NP dispersions.…”
Section: Colloidal Stability Of Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size reduction increases surface free energy which result in aggregation and destabilization of nanoparticals in suspension. Aggregation/fusion, sedimentation or creaming, crystal growth, change in crystal state are the major reason behind instability of nanoparticle in aqueous solvent [41]. Hence, to improve the long term stability of nanoparticles, colloidal suspension is converted into dry powder form using lyophilization.…”
Section: Small Moleculesmentioning
confidence: 99%
“…Current dry powder inhalers on the market have FPFs ranging between 10 and 70% [23]. Moreover, small size of NPs can lead to particle aggregation due to high surface energy thereby making handling of the NPs in dry powder form very difficult [2,24,25]. Therefore, the major challenge for pulmonary delivery of NPs is to find a proper carrier system with an MMAD suitable for pulmonary delivery [2,26].…”
Section: Introductionmentioning
confidence: 99%